2017
DOI: 10.1111/1346-8138.13787
|View full text |Cite
|
Sign up to set email alerts
|

Keratoacanthoma en plaque/nodule: A brief report of the clinicopathological features of five cases

Abstract: Keratoacanthoma (KA) is characterized by exoendophytic growth with a central keratin-filled crater, representing the crateriform architecture. We herein report five rare cases of KA without a central keratin-filled crater. These KA cases histopathologically showed that one or a few infundibular structures/isthmic lobules had their own open keratotic pores on the surface without a common merged keratotic plug/horn, clinically representing verrucous (keratotic) plaque/nodule, namely, "KA en plaque/nodule". KA ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…Some lesions exclude keratin plugs and also retain crateriform architecture, leaving an atrophic and hypopigmented scar 3,14 . Histopathologically, KA lesions show keratin‐filled, light, cup‐shaped structures and gradually lose the isthmic differentiation 11,12,14 . Our cases correspond to the second stage of KA.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Some lesions exclude keratin plugs and also retain crateriform architecture, leaving an atrophic and hypopigmented scar 3,14 . Histopathologically, KA lesions show keratin‐filled, light, cup‐shaped structures and gradually lose the isthmic differentiation 11,12,14 . Our cases correspond to the second stage of KA.…”
Section: Discussionmentioning
confidence: 60%
“…The first stage is the proliferative stage, in which the lesion grow to a diameter of 10‐25 mm within 6‐8 weeks, and the appearance from a macule turn to a papule, a volcano‐like form 3 . Histologic features of this phase are characterized by multiple, infundibular structures with keratin‐filled invaginations, which coincide with each other but do not form a merged keratotic plug/horn 11,12 . The second stage is the well‐developed stage, where the lesion stops growing, maintains its volcano‐like form, but may exhibit signs of rupture 3 .…”
Section: Discussionmentioning
confidence: 99%
“…In KA, the crateriform architecture is characteristic and can be recognized in most cases, but that is not essential. We previously reported cases having the same components as conventional KA without the crateriform architecture as keratoacanthoma en plaque/nodule [14] (Figure 1).…”
Section: Mutual Findings Among Stagesmentioning
confidence: 91%
“…It is defined as a keratoacanthoma without a central keratotic plug/ horn formed by contiguous, dilated infundibula. 1 Misago et al 1 reported that only five of 224 cases of keratoacanthoma met the criteria of keratoacanthoma en plaque. Reported dermoscopic findings of keratoacanthoma en plaque have been limited.…”
Section: Dermoscopic Findings In Two Cases Of Keratoacanthoma En Plaquementioning
confidence: 99%